Perbandingan Isolasi DNA Bakteri Escherichia coli dengan Metode Heat Treatment dan Filter Based Kit Berdasarkan Nilai Limit of Detection dan Limit of Quantification - Brillian Nur Muhammad; Zainul Fadli; Rio Risandiansyah (Jurnal Kedokteran Komunitas, 2020)
Introduction: One simple and rapid DNA isolation method is by heat treatment. However, it unknown whether the result of this method has the same quality compared to the more commonly used filter based kit. This research aims compare heat treatment and filter based kit DNA isolation methods based on its limit of detection (LOD) and limit of quantification (LOQ) from DNA isolation yield from E. coli.Method: This research is an in vitro laboratorium experimental research method. The E. coli concentration in this study is obtained through purposive samplingwith a concentration of 101 – 104 CFU/ml. Heat treatment and filter based kit method are DNA isolation methods used in this study. The data analysis uses ANOVA and Least Significant Diference (LSD) test.Result: Optimal yield of heat treatment method was found at a bacterial concentration of 10.000 CFU/ml (p=0.000) and 1000 CFU/ml (p=0.002). While the optimal yield of filter based kit was found at 10.000 CFU/ml (p=0.003), 1000 CFU/ml (p=0.009) and 100 CFU/ml (p=0.033). The purity value of both heat treatment and filter based kit method did not reach 1,7-2,0. The heat treatment's LOD was 2,39 ng/µl, while the filter based kit's LOD was 4,06 ng/µl. The heat treatment's LOQ was 6, 43 ng/µl, while the filter based kit's LOQ was 8, 10 ng/µl.Conclusion: According to limit of detection, the heat treatment method has the minimum bacterial concentration of 1000 CFU/ml. Whereas, the filter based kit method has the minimum bacterial concentration of 10 CFU/ml. Based on the method comparison, filter based kit method has higher yield than heat treatment method. Keyword: DNA isolation, heat treatment, filter based kit, Escherichia coli